Elementary Principals’ Views on the Policies and Practices of Paraeducators in Special Education - Douglas, Sarah N.; Bowles, Ryan P.; Kammes, Rebecca (Journal of the American Academy of Special Education Professionals, 2022)
Paraeducators are often utilized in the education of students with disabilities, and principals play key administrative roles with paraeducators. However, little research exists to understand principals’ experiences with paraeducators. This study explored principals’ perceptions regarding paraeducators in elementary settings. Given the varied educational policies across the U.S., we utilized a mixed-methods approach to explore the state context related to paraeducators and experiences of principals in one Midwestern U.S. state. Interviews were conducted with state department of education (DOE) employees to understand the educational context and policies. Then questionnaires were developed based on literature, DOE interviews, and feedback from experts and distributed to principals across the state using stratified random sampling. Qualitative and quantitative analyses were used to analyze questionnaire responses. Results indicate a lack of formal policies statewide, which led to varied practices. Principals identified a need for well-defined state level policies to support paraeducator hiring, training, supervision, and evaluation.